Modelling the Dynamic Air Transport Aviation Fuel Demand in India - Uttiya Bhattacharyya; Dr Dhalla Rizwan Salim (International Journal of Supply Chain Management, 2015)
This paper proposes a dynamic assessment of the aviation fuel demand and matches its supply in terms of price and quantity. It presents a perspective view of the aviation industry in terms of its contribution to the economy, challenges, aviation fuel demand and growth of passenger and freight traffic.A questionnaire survey is carried outto identify the various factors affecting the aviation fuel demand. Factor analysis is used to pick out the significant factors. A multiple regression model is developed to estimate the aviation fuel demand with factors like GDP, situations of negative publicity, price of fuel, competition from premium rail journey, promotions on tourism, cost of air freight, technological development in aircraft type and operation.Test data suggests that air passenger traffic and price of fuel are the main significant factors affecting aviation fuel demand in India. The model was validated with real data for FY 2011-12 with satisfactory results.The paper contributes in terms of a dynamic construct for aviation fuel demand assessment in India with introduction of a publicity index and concludes that the factors affecting the aviation fuel demand will change from time to time.